Raman spectroscopy of two-dimensional magnetic van der Waals materials - Kim, Kangwon; Lee, Jae Ung; Cheong, Hyeonsik (Nanotechnology, 2019)
Two-dimensional magnetic van der Waals (vdW) materials have attracted much interest recently. Magnetism in two dimensions is one of the most fascinating topics in condensed matter physics whereas atomically thin magnetic materials present new opportunities for novel spintronic devices. Raman spectroscopy has been established as an invaluable tool in the studies of such magnetic vdW materials as it has been found that the magnetic ordering, which is often difficult to probe directly in atomically thin samples, can be reliably monitored by Raman spectroscopy. Here, we review recent progress in using Raman spectroscopy for the study of magnetic vdW materials with the examples of Ising-type ferromagnet CrI3, Ising-type antiferromagnet FePS3, and XY-type antiferromagnet NiPS3. By monitoring characteristic spectroscopic signatures of magnetic ordering, one can probe various aspects of magnetic ordering.
Keywords: Antiferromagnets; Ferromagnets; Recent progress; Spectroscopic signatures; Spintronic device; Two-dimension; Van der waals; Raman spectroscopy; two-dimensional magnetic material; van der Waals material